Silicon quantum-dots-based optical probe for fluorometric detection of Cr6+ ions - Do, Duc Tho; Luyen, Van Nam; Nguyen, Thi Thanh Huyen; Pham, Manh Hung; Pham, Van Thang; Truong, Thi Ngoc Lien (Hue University Journal of Science: Natural Science, 2022)
In this report, silicon quantum dots (SiQDs) with the NH2 functional group were synthesized with the hydrothermal method. The as-prepared SiQDs exhibit a strong fluorescence emission peak at 441 nm when excited at 355 nm and are effectively quenched upon adding Cr6+ ions. Hence, SiQDs were used as an optical probe to detect Cr6+ ions in solutions. The crystal structure of SiQDs was characterized by using X-ray diffraction (XRD). The Fourier-transform infrared spectroscopy (FT-IR) was used to determine the linker groups on the SiQDs surface. The fluorescence spectroscopic technique with an excitation wavelength of 355 nm was used to quantify the Cr6+ ion concentration in the solutions in the range of 0.1–1000 µM. Competition from common coexisting ions, such as K+, Na+, Al3+, Zn2+, and Pb2+, was ignorable. The test with actual samples showed good linearity for the Cr6+ concentration range of 0.1–50 µM.